Seismic Characteristics and Mechanisms of Rockbursts - Bennett, T. J.; Marshall, M. E.; McLaughlin, K. L.; Barker, B. W.; Murphy, J. R. (1995)
Rockbursts and related mining-induced seismicity present several interesting problems for seismic monitoring of potential underground nuclear explosion tests. Such events occur in mining areas throughout the world and may be quite frequent at levels currently of interest for CTBT. The shallow focal depths of rockbursts prevent their discrimination from nuclear tests on the basis of depth identification. Many rockbursts also appear to be inefficient in excitation of long-period surface waves which negates the effectiveness of the traditional M sub S-vs-m sub b discriminant. This research project is aimed at finding alternative ways to identify rockbursts or related mine tremors. One additional aspect of interest is that mine tremors may be deliberately triggered, which could provide an evasion opportunity if timing of such events can be accurately predicted. Our investigations have focussed primarily on regional seismic signal characteristics and source mechanisms which may distinguish mine tremors from other source types. Over the past year or two, there have been several rockbursts in widely different tectonic environments. We have taken a close look at some of these events, including the February 3, 1995 (M = 5.2) mine collapse in southwestern Wyoming, the January 5, 1995 (M = 4.4) rockburst in the central Ural mountains, the October 30, 1994 (M = 5.6) mine tremor in South Africa, the March 11, 1995 (M = 4.0) mine bump in eastern Kentucky, and the March 12, 1994 (M = 3.6) mine collapse in northern New York. A consistent feature of the regional signals from all of these events appears to be relatively large S/P or Lg/P ratios. This behavior is similar to that seen in many earthquakes. The regional signals for rockbursts also often appear more complex than those from other source types. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p542-551.